Database reliability engineering : what, why, and how? (O'Reilly Media, 2017)
"SRE is becoming quite the ubiquitous term, but what about DBRE? Laine Campbell and Charity Majors dive into DBRE, exploring the paths to this craft and how to culturally evolve and support it. Laine and Charity focus on organizational scale, self-service, and force multipliers in recoverability, observability, availability, security, release management, and infrastructure."--Resource description page